Systematic Review and Meta‐Analysis of Locked Posterior Dislocation of the Shoulder Treated with Shoulder Arthroplasty: Improved Outcomes for Total Shoulder Arthroplasty are Associated with Increased Age - Matthew Crowley; Yasmine Ghattas; Andrew P. Collins; Samantha Levin; Benjamin C. Service (Orthopaedic Surgery, 2023)
Locked shoulder dislocations account for up to 5% of shoulder dislocations. These relatively rare injuries are characterized by dislocation of the humeral head from the scapular glenoid cavity with the humeral head incarcerated on the glenoid in a “locked” fashion. Diagnosis is often delayed because of the complexity of clinical presentation and subtle radiographic findings, resulting in locking of the humeral head out of the glenoid cavity with severe functional deficits. Most commonly, there are bony injuries to the glenoid and humeral head that engage and prevent closed reduction. Since few patients present with this injury, evidence‐based treatment guidelines have not been established. The objective of this review is to assess postoperative outcomes following shoulder arthroplasty for locked posterior shoulder dislocations (LPSD) to guide best practices for treatment. This systematic review was conducted following PRISMA guidelines, searching the PubMed and Web of Science databases for original articles assessing outcomes following arthroplasty for locked posterior shoulder dislocations. Seven publications that evaluated 102 patients were included. Additionally, nine case studies were included, assessing 20 shoulder arthroplasties. Overall, the analysis demonstrated significant improvement in shoulder pain following total shoulder arthroplasty (TSA) (P = 0.0003). Older operative patient ages for TSA resulted in significantly improved modified Neer outcomes scores and patient satisfaction compared to younger patients (P = 0.047). A positive correlation was noted for the duration of dislocation and necessity for revision surgery following hemiarthroplasty (HSA) and TSA combined and TSA separately. The risk ratios assessing the incidence of postoperative complications (RR = 0.56, 95% CI = 0.28–1.11) and necessity for revision surgery (RR = 0.58, 95% CI = 0.24–1.39) were insignificant but noted outcomes favoring TSA. Data from the included studies show that both TSA and HSA are efficacious at treating locked posterior shoulder dislocation. Postoperative outcomes following TSA versus HSA are similar. TSA may be a more efficacious surgical treatment in elderly patients, with improved outcomes and patient satisfaction scores compared to younger patients. Early diagnosis and treatment of posterior locked dislocations may lead to reduced postoperative complications and revision surgery, signaling the importance of proper injury investigation and early treatment. The role of RSA in the management of locked posterior shoulder dislocation remains to be determined, as there is insufficient clinical outcome data currently in the literature.